Influence of fertilizer rates on growth of selected immature rubber (Hevea brasiliensis Muell. Arg) clones grown on two soil series - Adekunle, Salisu Monsuru (2014)
Knowledge of fertilizer required for (Hevea brasilieinsis) latex timber clones (LTC) is necessary to evaluate how fertilizer levels influence the growth and yield performance of young rubber under micro-environmental conditions. This will enable rubber industry to meet the increasing global demand of natural rubber. This study aims at evaluating the influence of fertilizer rates currently recommended by Rubber Industry Smallholders Development Authority (RISDA 1) for rubber growers in Malaysia. It is a compound fertilizer with the following composition (N10.7, P 16.6, K 9.5, Mg 2.4). This study identifies the fertilizer level that could be used in planning nutritional program for latex timber clones (LTC) Hevea brasiliensis at immature stage. Factorial experimental design (with two factors) was used to study forty five seedlings from three selected rubber clones planted in polybag on two different soil series (Munchong and Holyrood) each. These rubber clones (RRIM 2001, RRIM 2025 and RRIM 3001) were collected from Malaysia Rubber Board and planted in 15 x 33 cm polybags size filled with 15 kg soil. The seedlings, planted on two soils, Munchong and Holyrood (classified as Ultisols and Oxisol soils) are placed under rain shelter. The treatments consist of four fertilizer rates and a control. F1 0 g/plant (Control), F2 (78 g/plant), F3 (156 g/plant), F4 (234 g/plant) and F5 (312 g/plant) are used as treatments for each clone. Data on physiological and morphological traits such as plant height, girth size, and chlorophyll content were collected for one year. Roots image analysis for root length, root volume, average diameter and surface area were measured using WinRHIZO root scanning machine. Foliar analysis was conducted to determine nutrient acquisition of these clones. Plant growth parameters showed that, RRIM 3001 and RRIM 2001 clones significantly responded to fertilizer rates in terms of plant girth size. In the case of RRIM 3001 increased girth size on both soils was seen when fertilizer reached maximum level of 224 g/plant. This showed that clone RRIM 3001 performed best followed by RRIM2001 and RRIM 2025. Considering the importance of girth size in rubber cultivation, fertilizer rate 224 g/plant could be recommended as optimum level for plant growth in nursery program. Foliar analysis showed that different clones require different nutrient concentrations. The clones significantly responded to increasing N, P, K and Mg. It can be deduced from the study that RRIM 3001 judiciously utilized nutrient followed by RRIM 2001. Although, all the clones except RRIM 2001 may require more P concentration when planted on both soils in order to meet its nutritional requirement. The root analysis showed that fertilizer had significant influence on the root morphological traits. It was observed that RRIM 3001 significantly responded based on all the root morphological traits measured except root surface area and root length on both soil followed by RRIM 2025. It can be concluded that RRIM 3001 had performed best in root morphological traits compared to other clones. Fertilizer recommendation by RISDA could be adopted because it facilitate root growth which help nutrients uptakes. With thorough monitoring and measurement of plants growth performance, nutrient concentration and root growth, it can be concluded that fertilizer recommendation should be based on the genetic background, soil type in a given area and other growing factors. The seedlings of latex timber clones (LTC) RRIM 3001 could be recommended on Munchong and Holyrood soil with balanced fertilizer recommendation. From this study, fertilizer rate 224 g/plant could be recommended as optimum level. However, further trial (field) needs to be to be carried on RRIM 2001, RRIM 2025 and RRIM 3001 to validate the output of this study. Finally, fertilizer rates recommended by RISDA could be adopted in nursery practices with continuous evaluation so as to meet the growth and nutritional needs of Hevea for both new and existing clones. This will help the industry to successfully raise advanced planting materials of natural rubber.